2010
DOI: 10.1038/ejcn.2009.143
|View full text |Cite
|
Sign up to set email alerts
|

Serum folate and homocysteine and depressive symptoms among Japanese men and women

Abstract: Background/Objectives: Folate and homocysteine have been implicated to have a role in depression. However, results of epidemiologic studies on this issue have been inconsistent. The objective of this study was to clarify the association between serum folate and homocysteine concentrations and depressive symptoms in Japanese adults. Subjects/Methods: We analyzed cross-sectional data for 530 municipal employees (313 men and 217 women), aged 21-67 years, who participated in a health survey at the time of periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 33 publications
4
33
1
2
Order By: Relevance
“…France (Astorg, et al, 2008), Greece (Dimopoulos, et al, 2007), Japan (Murakami, et al, 2008;Nanri, Mizoue, et al, 2010) Norway (Bjelland, et al, 2003), Singapore (Ng, Niti, Zaw, & Kua, 2009), Spain (Sanchez-Villegas, Doreste, et al, 2009Sanchez-Villegas, et al, 2006), and Australia before 2009 (Almeida, et al, 2010;Sachdev et al, 2005). Fortification of flour with folic acid may have attenuated the effect of folate, which corroborates the aforementioned hypothesis that lower vitamin status may be more strongly associated with depression compared to higher vitamin status due to mandatory fortification.…”
Section: Discussionmentioning
confidence: 99%
“…France (Astorg, et al, 2008), Greece (Dimopoulos, et al, 2007), Japan (Murakami, et al, 2008;Nanri, Mizoue, et al, 2010) Norway (Bjelland, et al, 2003), Singapore (Ng, Niti, Zaw, & Kua, 2009), Spain (Sanchez-Villegas, Doreste, et al, 2009Sanchez-Villegas, et al, 2006), and Australia before 2009 (Almeida, et al, 2010;Sachdev et al, 2005). Fortification of flour with folic acid may have attenuated the effect of folate, which corroborates the aforementioned hypothesis that lower vitamin status may be more strongly associated with depression compared to higher vitamin status due to mandatory fortification.…”
Section: Discussionmentioning
confidence: 99%
“…The study procedure has been described in greater details elsewhere (Murakami et al, 2008;Nanri et al, 2010). In brief, the survey was conducted in July and November 2006 among employees working in two municipal offices in northeastern Kyushu, Japan.…”
Section: Study Subjects and Proceduresmentioning
confidence: 99%
“…Previously, the effect of PS on diet (5)(6)(7)(8) and the effect of drinking on diet (10)(11)(12) were investigated separately. In the present study, we fi rst reported the interaction between self-reported PS levels and drinking status in relation to diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few studies of the effect of drinking on diet in Japanese subjects. The effect of PS on diet (5)(6)(7)(8) and the effect of drinking on diet (10)(11)(12) are well documented, but little is known about the combined effect of PS and drinking on diet. Our objective was to investigate interactions between PS levels and drinking status in relation to dietary intake of food and nutrients in a large-scale cross-sectional study of middle-aged Japanese men and women.…”
Section: Interactions Between Psychological Stress and Drinking Statumentioning
confidence: 99%
See 1 more Smart Citation